1981
DOI: 10.1063/1.442139
|View full text |Cite
|
Sign up to set email alerts
|

The dielectric properties of ice Ih in the range 272–133 K

Abstract: The amplitude of the orientational dielectric dispersion of impure polycrystalline ice Ih has been measured at temperatures down to 133 K in an attempt to find evidence for an ordering transition. The Curie–Weiss temperature is 6.2±1.7 K and so, within the experimental precision, there is no significant evidence that the molecular orientations become more correlated than the ice rules require. From the most recent results on polycrystalline ice, the Curie–Weiss temperature is 15±∼11 K. As this temperature is f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
204
2

Year Published

1982
1982
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(232 citation statements)
references
References 22 publications
26
204
2
Order By: Relevance
“…The value of 0.28 eV is close to the value of 0.25 eV obtained from depolarization thermocurrent measurements for the activation energy of the low temperature DTC peak (at about 125 K) in pure ice [15]. The following explanation can be given for the observed shift to a lower activation energy in pure ice at low temperatures [16]: Water molecules in pure ice are reorientated by the diffusion of Bjerrum D-and L-defects. The activation energy of the dielectric relaxation of 0.62 eV at high temperatures is due to the production and motion of intrinsically generated D-and L-defects.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The value of 0.28 eV is close to the value of 0.25 eV obtained from depolarization thermocurrent measurements for the activation energy of the low temperature DTC peak (at about 125 K) in pure ice [15]. The following explanation can be given for the observed shift to a lower activation energy in pure ice at low temperatures [16]: Water molecules in pure ice are reorientated by the diffusion of Bjerrum D-and L-defects. The activation energy of the dielectric relaxation of 0.62 eV at high temperatures is due to the production and motion of intrinsically generated D-and L-defects.…”
Section: Discussionmentioning
confidence: 68%
“…Taking into account the interpretation of Johari and Whalley [16] for the T-dependence of W in pure ice, we conclude that this indicates that in W/O suspensions extrinsically generated D-and L-defects dominate over the intrinsically generated D-and L-defects in the whole temperature range. As for the extrinsic defects that generate D-and L-defects, we suggest that they must be physical defects whose concentration in frozen W/O suspensions is high due to supercooling breakdown.…”
Section: Discussionmentioning
confidence: 99%
“…The value commonly used for water is 78.5, which corresponds to the liquid state at room temperature. For the solid state, it has been shown that increases sharply with decreasing temperatures (Johari & Jones 1976;Johari & Whalley 1981). A value of = 600 was extrapolated from this comprehensive study for temperatures in the range of 10 to 50 K corresponding to the conditions of both the experiments and the ISM.…”
Section: The Ice Modelmentioning
confidence: 99%
“…The cavity is created inside a uniform medium characterized by a dielectric constant that is a function of temperature. A value of 600, extrapolated from the results obtained in a comprehensive study of the dielectric constant of water as a function of temperature (Johari & Jones 1976;Johari & Whalley 1981) was employed in the present modeling of the interstellar ices at (10−50 K), instead of the usual value of 80 for liquid water. We also computed the dipole moments along the main rotation axis for each isomer of neutral glycine, even though we are aware that they are of limited help to radio-astronomers, as the spectrum of molecules with several functional groups is complex and by no means predictible based on dipole moments only.…”
Section: Computational Backgroundmentioning
confidence: 99%